Work engagement and its antecedents in remote work: A person-centered view - Mäkikangas, Anne; Juutinen, Soile; Mäkiniemi, Jaana-Piia; Sjöblom, Kirsi; Oksanen, Atte (Work and stress, 2022)
The aim of this study was to investigate characteristics associated with employees' ability to cope with the challenges of remote working as flexible work arrangements are predicted to constitute an increasingly pervasive model of work. More specifically, we investigated job resources specific to remote work and employees' strengths and behaviours that may be crucial for enhancing work engagement when working outside a traditional office environment. The present study adopted a person-centered approach to investigate work engagement and its antecedents. A sample of 455 employees completed a questionnaire four times across a ten-month period during the enforced remote work occasioned in response to the corona pandemic. The results revealed four distinct work engagement profiles. Most employees (75%) belong to profiles with either average or high levels of work engagement, which remained stable after a slight initial increase. A decrease was observed in 25% of those employees whose work engagement was already low at the study baseline. High levels of organisational support, the functionality of home as a work environment, job-related self-efficacy, and job crafting characterised the profile in which work engagement remained at a high level during the remote work. Implications for practice concerning well-being protective multi-locational work are presented.